2001
DOI: 10.1007/bf01280314
|View full text |Cite
|
Sign up to set email alerts
|

Wall ingrowth architecture in epidermal transfer cells ofVicia faba cotyledons

Abstract: We describe the use of scanning electron microscopy to provide novel views of the three-dimensional morphology of the ingrowth wall in epidermal transfer cells of cotyledons of developing Vicia faba seed. Wall ingrowth deposition in these cells amplifies the surface area of plasma membrane available for transport of solutes during cotyledon development. Despite the physiological importance of such amplification, little is known about wall ingrowth morphology and deposition in transfer cells. A detailed morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 37 publications
1
51
0
1
Order By: Relevance
“…According to DeWitt et al (1999) and Thompson et al (2001), the number of folds in such cell walls is responsible for the increasing of plasmalema surfaces and leads to the transport of solutes in the seeds. In Leguminosae, labyrinth wall cells were observed in the inner layers of the seed testa and in the cotyledon epidermis of the seeds in Vicia faba (Talbot et al, 2001;Thompson et al, 2001) and not in the endosperm, as in C. ferrea. Before germination, the position of the labyrinth face in the cell showed that in the mature seeds of C. ferrea, the transport of nutrients was polarized towards the embryo, which was confirmed by the presence of a large amount of starch grains in the embryonary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…According to DeWitt et al (1999) and Thompson et al (2001), the number of folds in such cell walls is responsible for the increasing of plasmalema surfaces and leads to the transport of solutes in the seeds. In Leguminosae, labyrinth wall cells were observed in the inner layers of the seed testa and in the cotyledon epidermis of the seeds in Vicia faba (Talbot et al, 2001;Thompson et al, 2001) and not in the endosperm, as in C. ferrea. Before germination, the position of the labyrinth face in the cell showed that in the mature seeds of C. ferrea, the transport of nutrients was polarized towards the embryo, which was confirmed by the presence of a large amount of starch grains in the embryonary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tais projeções do protoplasto parecem ser exclusivas da epiderme na face adaxial. Elas constituem invaginações da membrana plasmática que se assemelham àquelas encontradas em células de transferência, sendo acompanhadas pela correspondente deposição de parede celular, as chamadas introjeções da parede ("wall ingrowths", conforme Gunning & Pate 1969;Talbot et al 2001;Offler et al 2002). Estudos complementares são necessários para esclarecer se as células epidérmicas com projeções protoplasmáticas funcionam ou não como células de transferência, investigando se haveria troca de substâncias através das mesmas.…”
Section: Discussionunclassified
“…When expansion is completed, some plant cells produce a thick secondary wall (Talbot et al 2001). In transfer cells the thickness of the secondary wall is not uniformly formed by invaginated projections, which characterize these cell types (Gunning and Pate 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this specialization, transfer cells are found in various organs, such as gametophytic cells (Diboll and Larson 1966, Cass 1972, Wilms 1981, Bohdanowicz and Turała-Szybowska 1985 and vascular tissues, specifically in the parenchyma 528 THÁLIA S.S. GAMA, ANA CRISTINA A. DE AGUIAR-DIAS and DIEGO DEMARCO cells of the xylem and companion cells of the phloem , Gunning et al 1970, Talbot et al 2002. Transfer cells, due to their function of intensifying the transport of solutes over short distances, play a very important role in secretory structures that require this flow to release substances (Offler et al 2003).…”
Section: Introductionmentioning
confidence: 99%